IMPOSITIVE SPEAKING ACTIONS IN THE COLLECTION OF TUNAS KARYA EKO TUNAS SHORT STORIES AND THEIR IMPLICATIONS FOR LEARNING INDONESIAN LANGUAGE IN SMA (A PRAGMATIC STUDY) - Windi Listiyawati; Afsun Aulia Nirmala; Wahyu Asriyani (Universitas Ngudi Waluyo, 2021)
AbstractIt is known that language is an interaction tool that plays an important role in life to convey certain goals and objectives. One needs to understand the basic principles of language and understand the ethics of language politeness in order to avoid conflicts in social life. Language is a differentiator between individuals. Talking about the relationship between language and pragmatics which is a principle in language, namely two branches of linguistics that complement each other in use in everyday life. In everyday life, a person communicates with a speech partner, without realizing it contains a speech act. The purpose of this study is to describe the types of speech acts in the collection of short stories by Eko Tunas and to find out the implications of directive speech acts in the collection of short stories by Eko Tunas for learning Indonesian in high school. This research is descriptive qualitative and uses a qualitative approach. This research procedure consists of 3 stages, namely the pre-research stage, the implementation stage, and the completion stage. The data source is the book collection of short stories Tunas by Eko Tunas. Techniques for providing data are basic reading techniques and advanced note-taking techniques. Presentation of data using informal methods. It can be concluded that there are 30 data in 21 types of short stories consisting of directive speech acts requestives (1 data), directive speech act probobitives (0/none), directive speech act question (23 data), directive speech act requirements (2 data), directive speech acts advisories (4 data), directive speech acts permissive (0/none). This research can be implicated in Indonesian language learning in SMA class XI at KD 3.9 and 4.9 which relates to material about analyzing the building blocks of short stories in a collection of short stories and constructing a short story by paying attention to the elements of building short stories.